(untitled) (Third Sector Social Economic Review, 2024)
This study aimed to reveal the reasons for leaving work and the turnover rate of non-physician healthcare personnel between 2017 and 2021 in a tertiary private hospital in Ankara. In this retrospective cross-sectional study, the hospital’s human resources records between 2017 and 2021 were scanned. Data on the reasons for leaving their jobs were recorded. The findings were presented in frequency, percentage, and graphs. The personnel turnover rate of healthcare professionals within the research varies between 5.5% and 12.5% between 2017 and 2021. The personnel turnover rates and their reasons varied over time. The most important reason for healthcare workers leaving their jobs in private hospitals was determined to be financial security. Healthcare workers preferred to work in the government or leave their jobs for a better wage. The turnover rate was higher at a younger age. Many reasons push healthcare professionals to leave their jobs. The reasons and rate of quitting vary significantly depending on time and location. At this point, health and human resources managers need to take a situational approach, read the conditions of the place and time well, and choose proactive methods that will increase the organizational commitment of experienced personnel.